Alih Kode dan Campur Kode dalam Interaksi pada Grup Whatsapp Mahasiswa Program Studi Pendidikan Bahasa dan Sastra Indonesia Universitas Persatuan Guru 1945 NTT - Onsri Henukh; Richard Oematan; Ronni M. Ndun (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
The problems raised in this study are: (1) What are the forms of code-switching and code-mixing used by students of the Indonesian Language Education Study Program in the WhatsApp group? (2) What factors influence the occurrence of code-switching and code-mixing in the group? (3) What are the functions of using code-switching and code-mixing in student communication within the WhatsApp group? The objectives of this study are: (1) To describe the forms of code-switching and code-mixing in student interactions within the WhatsApp group. (2) To analyze the factors causing the use of code-switching and code-mixing in student communication. (3) To explain the social functions of using code-switching and code-mixing in digital academic communication. The method used in this study is a qualitative descriptive method. The data collection techniques employed are non-participant observation, documentation, and interviews. The results of the study show that: (1) the forms of code-switching found include internal, external, and metaphorical code-switching, while the forms of code-mixing include word, phrase, and clause code-mixing, with code-mixing being the most dominant form; (2) the factors causing code-switching and code-mixing include social, situational, linguistic, and digital media factors; (3) the functions of using code-switching and code-mixing include communicative, social, expressive, and identity functions.